Knowledge Translation and Moving Towards Improving Childbearing in Iran - Jalali, Tahereh (Shahroud Journal of Medical Sciences, 2025)
The modern world, alongside the expansion of opportunities and transformation of aspirations, has led to a delay in childbearing.The Islamic Republic of Iran is one of the leading countries in the sharp decline in fertility rates, dropping from a fertility rate of 7 in 1980 to 1.9 in 2006. This decline aligns with the global trend of decreasing fertility rates, which began in Western societies with France and in non-Western societies with Japan. Scholars have identified Westernization as the main factor in fertility transition in non-Western societies, which are not as socio-economically modern. This includes an emphasis on nuclear families and the belief that the costs of children outweigh their potential benefits. Recent interpretations of contemporary societies address the role of development with broader impacts compared to cultural and ideological changes.